Role of pseudomonas fluorescens as PGPR in cadmium stress alleviation in vigna radiata (mung beans) - ABHILASHA SHOURIE; U.VIJAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2018)
Cadmium toxicity in crop plants is one of the major concerns and is responsible for the loss in yields. This investigation analyses the role of a common PGPR Pseudomonas fluorescens, in alleviating cadmium stress in Vigna radiata seedlings. The seedlings were exposed to Cd stress at different levels i.e. 0, 100 and 200 ppm and physiological response was observed in PGPR treated and untreated plants. The growth and biomass of mung bean seedlings were reduced to considerable extent whereas MDA content increased with exposure to increasing cadmium concentrations. Treatment with P. fluorescence showed remarkable improvement in growth, biomass and production of stress combating metabolites proline and flavonoids, and reduced MDA content. The study showed that the ameliorative effects of P. fluorescens involved the prevention of H2O2 accumulation in mung bean shoots, which is an important signaling molecule produced during Cd stress.